Balancing client preferences and population-level goals: a qualitative study of the ways in which public health providers and facility administrators interpret and incentivise quality of care in contraceptive counselling in Ethiopia, Mexico and India - Lauren Suchman; Janelli Vallin; Ximena Quintero Veloz; Lakhwani Kanchan; Ewenat Gebrehanna; Bella Uttekar; Reiley Reed; Lorena Santos; Kelsey Holt (Sexual and Reproductive Health Matters)
Recent work in family planning has shifted from an instrumentalist perspective on quality in contraceptive counselling, which views quality as a means to encourage contraceptive uptake, to privilege quality of care as a valued end in itself. In this context of shifting narratives about quality, it is important to understand how health systems and providers navigate potential conflicts between instrumentalist definitions of quality versus a person-centred definition that considers meeting clients’ contraceptive needs and preferences as an important end goal in and of itself. However, we know little about how providers and other health system stakeholders interpret the concept of quality in counselling, and how their experiences with different quality monitoring systems influence their ability to provide person-centred care. This qualitative study draws from 51 in-depth interviews with public healthcare providers and health facility administrators in Ethiopia, Mexico and India. Across all three countries, except for some cases in India, administrators were concerned with encouraging uptake of contraceptives in order to meet local and national level goals on contraceptive uptake and maternal health. In contrast, providers were more concerned with responding to client desires and needs. However, participants across all levels shared the opinion that successful counselling should end with contraceptive uptake. We conclude that the instrumentalist view of quality counselling continues to prevail across all three countries. Our findings suggest that encouraging healthcare providers and administrators to meet even relatively broad targets set by government reinforces an instrumentalist approach, as opposed to an approach that privileges person-centred care.